Validation of gene and quantitative trait loci associated with Nilaparvata lugens Stål resistance in Oryza sativa L. cultivar Rathu Heenati - Md Yusoff, Ruziah (2018)
The use of resistant varieties has been recognized as more economical and environmental friendly approach to manage brown planthopper Nilaparvata lugens Stål (BPH) populations in the rice fields. Rathu Heenati has a broad spectrum resistance against BPH. At least, four genes and QTLs were reported in Rathu Heenati, namely Bph3 located on chromosome 6, Qbph3 (Chr 3), Qbph4 (Chr 4), and Qbph10 (Chr 10). Microsatellite markers, flanking these gene/QTLs has been identified and made available in the literatures. This study was aimed to validate the presence of those gene/QTLs in Rathu Heenati by using the F2 population of a cross between Rathu Heenati/MR219 with the final aim to introgress them into MR219 through marker-assisted selection (MAS). Resistance assessment were based on plant damage score (a measure of tolerance) and amount of honeydew excretion (a measure of antibiosis) while the presence of the gene/QTLs in the individual F2 plants was based on the polymorphism of their respective markers on F2 plants, Qbph3 (RM7 and RM1256), Qbph4 (RM8213 and RM5473), Bph3 (RM8072 and RM588) and Qbph10 (RM5352, RM228 and RM5471). Levels of resistance of individual plants were estimated. Cluster analysis manages to divide the plants into four clusters at 0.06 semi partial R-square value. These clusters represent groups of resistant plants (IV), moderately resistant (III), moderately susceptible (II), and susceptible (I). Correlation analysis showed significant correlation between Bph3 presence and the amount of honeydew excretion (r = -0.200*), while Qbph10 presence is correlated with the plant damage score (r = -0.196*). There was no correlation observed between Qbph3 or Qbph4 presence to any of the two phenotypic parameters measured. This study indicated that the presence of Bph3 and Qbph4 from Rathu Heenati contributed to the BPH resistance among the progenies of Rathu Heenati/MR219 cross. Their flanking markers were successfully utilised in the marker-assisted selection to monitor the gene introgression among the progenies of the cross. There were 59 F2 plants in the group IV which are resistant to BPH which could be promoted for further evaluation at the F3 generation.